2021
DOI: 10.1080/13621718.2021.1880816
|View full text |Cite
|
Sign up to set email alerts
|

Liquid metal embrittlement during the resistance spot welding of galvannealed steels: synergy of liquid Zn, α-Fe(Zn) and tensile stress

Abstract: In this study, the influence of the microstructural evolution of galvannealed (GA) coating and the thermomechanical characteristics of liquid metal embrittlement (LME) cracking during resistance spot welding (RSW) of steels were investigated. The analysis of LME cracks, coating microstructure and thermomechanical characteristics at various weld regions revealed a synergistic effect of liquid Zn, α-Fe(Zn), and tensile stress on LME cracking during RSW. A continuous α-Fe(Zn) layer inhibits liquid Zn from contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Low strain rates combined with high temperatures are the reason for the formation of these intermetallic phases [ 14 ]. The intermetallic phases form at the interface of Fe-Zn and suppress the contact between steel and liquid zinc while acting as a protection layer of the base steel [ 33 ]. High-magnitude tensile stresses can cause fracture of the α-Fe(Zn) layer and continue in the steel sheet, while liquid zinc can penetrate the cracks and initiate LME.…”
Section: Resultsmentioning
confidence: 99%
“…Low strain rates combined with high temperatures are the reason for the formation of these intermetallic phases [ 14 ]. The intermetallic phases form at the interface of Fe-Zn and suppress the contact between steel and liquid zinc while acting as a protection layer of the base steel [ 33 ]. High-magnitude tensile stresses can cause fracture of the α-Fe(Zn) layer and continue in the steel sheet, while liquid zinc can penetrate the cracks and initiate LME.…”
Section: Resultsmentioning
confidence: 99%
“…7 The main drawback of analysing LME cracking using the HTTT test is the inherent differences in RSW thermal cycles and the simulated thermal cycles during HTTT tests. 6 Differences in HTTT parameters such as set temperature, hold time, and strain rate can result in discrepancies in the thermal cycles and LME cracking behaviour. Moreover, it has been shown that these parameters can influence the morphology and microstructure of the Fe–Zn intermetallic in the coating layer, which is critical to LME cracking behaviour assessment 7,8 Discrepancies in the Fe–Zn intermetallic compound morphology between HTTT and RSW have been reported and attributed to different thermal cycles of each process.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown that these parameters can influence the morphology and microstructure of the Fe–Zn intermetallic in the coating layer, which is critical to LME cracking behaviour assessment 7,8 Discrepancies in the Fe–Zn intermetallic compound morphology between HTTT and RSW have been reported and attributed to different thermal cycles of each process. 6…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations